Dielectric properties and electromagnetic interference shielding studies of nickel oxide and tungsten oxide reinforced polyvinylchloride nanocomposites. Issue 15 (12th October 2020) - Muzaffar, Aqib; Ahamed, M. Basheer; Deshmukh, Kalim; Pasha, S. K. Khadheer
ABSTRACT: Polyvinylchloride (PVC)/nickel oxide (NiO)/tungsten oxide (WO3 ) nanocomposite films were prepared via solution casting technique. The crystallinity, morphology, and the analysis of dispersion state of PVC/NiO/WO3 nanocomposite was carried out using X-ray diffraction (XRD) and scanning electron microscopy (SEM). The dielectric studies of nanocomposite films were investigated and a maximum dielectric constant of 2.3 with dielectric loss (tan δ) of 2.4 was attained. The EMI shielding studies were carried out in the X and Ku-band frequency range (8 GHz-18 GHz). The maximum SE of 15.78 dB in X-band and 12.05 dB in Ku-band was achieved for 75/20/5 compositions of the PVC/NiO/WO3 nanocomposite. GRAPHICAL ABSTRACT: